Credit Market Liberalization Reform Outcomes - Zukhba, D.S.; Shpynova, K.V. (Економічний вісник Донбасу, 2013)
This article deals with the process of credit market liberalisation in different countries and the main tools for conducting the reform. The impact of financial liberalisation on economic growth in the most developed countries has been determined. The article represents the basic indicators of economic development in countries with the most developed credit markets. У цій статті розглянуто процес лібералізації кредитних ринків різних країн та основні інструменти проведення реформи. Відображено вплив фінансової лібералізації на економічне зростання найбільш розвинутих країн. Представлено основні показники економічного розвитку країн із найбільш розвинутими кредитними ринками. В данной статье рассмотрен процесс либерализации кредитных рынков разных стран и основные инструменты проведения реформы. Отображено влияние финансовой либерализации на экономический рост наиболее развитых стран. Представлены основные показатели экономического развития стран с наиболее развитыми кредитными рынками.